Modeling the determinants of cigarette consumption in Iranian households with children under 5 years of age using the Income and Expenditure Survey 2021 - Shakila Bagheri; Naser Kamyari; Saeed Hesam; Maryam Seyedtabib (Archives of Public Health)
Abstract Background Cigarette smoking remains a significant public health concern, with detrimental effects on both smokers and those exposed to secondhand smoke. This study investigates the factors influencing smoking behaviors in Iranian households, focusing on households with children under five years old. Methods We conducted a cross-sectional analysis of 8751 Iranian households using data from the Iranian Household Income and Expenditure Survey (HIES) collected by the Statistical Center of Iran (SCI) in 2021. A variety of count regression models were examined, including Poisson (P), Negative Binomial (NB), Generalized Poisson (GP) and their zero-inflated counterparts. The best fitting model was selected based on goodness-of-fit indices. Results Approximately 87% of households were non-smokers, with a mean daily cigarette consumption of 14.29 (SD = 8.64) among smokers. The three-level Zero-Inflated Generalized Poisson (TL-ZIGP) model was considered a suitable model for the interpretation of the data. Key predictors of smoking included older age, male gender, lower education, higher income, and larger homes. Homeownership was negatively associated with smoking. Considerable geographic variation in smoking prevalence was observed. Conclusions Socioeconomic and demographic factors, including lifestyle and geographic regions, are associated with smoking behavior among Iranian households. A three-level ZIGP regression model is appropriate for analyzing these complex relationships. This study reveals different patterns of smoking prevalence in different population subgroups and emphasizes the need for targeted interventions to effectively reduce smoking rates.